THE EFFECT OF PROBLEM BASED LEARNING MODELS BASED ON SOCIO-SCIENTIFIC ISSUES ON STUDENTS' CRITICAL THINKING SKILLS ON HYDROCARBON BURNING MATERIALS - Ardianti, Dewi Linda; Feronika, Tonih; Wardani, Miessya (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2024)
Critical thinking skills in high school chemistry are still relatively low. One of the factors that causes students' low critical thinking skills is teachers who still dominate learning activities. This research aims to determine the effect of the Problem Based Learning (PBL) model based on Socio-scientific Issues (SSI) on students' critical thinking skills on hydrocarbon combustion material. This research was carried out at SMAN 11 South Tangerang City. The research method used in this research is a quantitative method with a quasi-experimental research method. The research sample was XI IPA 1A (as the experimental class) and XI IPA 1B (as the control class) with 16 students each. The instrument used was a description test with 22 questions representing 12 indicators of Robert H. Ennis' critical thinking. The results of the N-Gain data hypothesis test using the t-test (Independent Sample t Test) obtained a sig (2-tailed) < ?, namely 0.00 < 0.05 so H1 was accepted and H0 was rejected. This shows the influence of the problem based learning model based on socio-scientific issues on students' critical thinking skills on hydrocarbon combustion material.